Model Dinamik Pengelolaan Jasa Ekosistem Waduk Koto Panjang Kabupaten Kampar Riau - Trisla Warningsih; D Djoko Setiyanto; Achmad Fahrudin; Luky Adrianto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
The study aims to establish the management model of ecosystem services Koto Panjang Reservoir.The approach used in this modeling is the Dynamic Modelling. The results showed the value ofprediction error of the simulation results based on the data used was in the range 0.4 % - 4.64 %. Thesimulation results show the value of economic growth in 2020 will reach its peak value Rp.3,3 billion.The economic value of the total economic value of the four main activities of the utilization ofecosystem services Koto Panjang Reservoir namely; KJA cultivation of Rp.1,1 billion, tourism Rp.1,6billion, fishing by paddle for 60 million, fishing by fishing boat engine at Rp.489 million. Modelscenarios developed by increasing the KJA growth of 30% and 100% for tourism, managed toincrease the total economic value of Rp.5,08 billion from previously around Rp.3,3 billion or anincrease of approximately 53.95%. The increase in the economic value derived from an increase inthe economic value of Rp.1,56 billion KJA activities and improvement of the economic value oftourism activities Rp 2,9 billion. Keywords: ecosystem services, reservoirs, total economic value, dynamic modelling